Analisis Faktor Faktor yang Berhubungan dengan Tingkat Kelelahan Mata di PT. Total Enviro Solusindo - Fahru Roji; Munaya Fauziah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to determine the relationship between individual and environmental factors with the level of eye fatigue in employees. This quantitative study used a cross-sectional design. A total of 60 respondents were selected using total sampling. Data were collected through questionnaires and analyzed using the chi-square test. The variables assessed included age, gender, history of visual impairment, duration of screen use, and lighting intensity in the workplace. The results showed that only gender had a statistically significant association with eyestrain (p = 0.034). Other variables-age (p = 0.859), history of visual impairment (p = 0.482), duration of screen use (p = 0.764), and lighting intensity (p = 0.158)-had no significant association. Most respondents (71.7%) experienced moderate levels of eyestrain. Gender was the only factor significantly associated with eyestrain in administrative workers. While other variables did not show a significant relationship, they are still relevant in the effort to maintain eye health in the workplace.